IDENTIFICATION OF INTESTINAL MICROBES IN CHILDREN WITH DIARRHEA ANDNON-DIARRHEA USING POLYMERASE CHAIN REACTION / ELECTROSPRAY IONIZATION-MASS SPECTROMETRY (PCR / ESI-MS) - Teguh Sarry Hartono; Dewi Murniati; Andi Yasmon; Lucky H Moehario (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2015)
Abstract :Microbiota present in human intestinal are diverse, and imbalance in composition of intestinal flora may cause diarrhea.This study aimed to obtain a profile of intestinal bacteria in children with and without diarrhea and assess their presence with incidence of diarrhea. An analitical descriptive with cross sectional design study was carried out. A stool specimen was collected from each children of 2-12 years old with and without diarrhea who lived in North Jakarta. DNA extraction was performed prior to detection of microbes using Polymerase Chain Ceaction/Electrospray Ionization-Mass Spectrometry.Eighty stool specimens consisted of 33 and 47 specimens from children with and without diarrhea were included in the study. Thirty single and 6 multiple matches were detected in 30 specimens of the diarrhea group; 28 single and 8 multiple matches were found in 34 specimens of the non-diarrhea.Escherechiacoli and Klebsiella pneumonia were predominant in both groups. Firmicutes, Proteobacteria and Bacteroidetes were deteced in the diarrhea group, while Actinobacteria, Proteobacteria and Verrucomicrobia were in the non-diarrhea. The relationship of incidence of diarrhea and the present of enteropathogens in the stool was not significant, however, there was a strong correlation of the risk of suffering diarrhea due to the presence of enteropathogens (OR = 0.724 with 95%, CI: 0.237-2.215).In conclusion, most bacteria detected in both groups were similar, nonetheless, Actinobacteria was present only in the non-diarrhea. The chance to have diarrhea was higher when enteropathogen was detected in the stool.